Treatment-refractory schizophrenia : a clinical conundrum - Gaughran, Fiona; Buckley, Peter F. (Springer Berlin Heidelberg, 2014)
Schizophrenia is often associated with an inadequate response to pharmacological and non-pharmacological treatments. How to treat patients who have an unsatisfactory response to anti-psychotics, including clozapine - which is unequivocally the most powerful antipsychotic medication for this recalcitrant population  - remains a clinical conundrum. A range of adjunctive medications have been tried with mixed results; there has also been renewed interest in the role of neuromodulatory strategies, electroconvulsive therapy, and cognitive and vocational approaches. Perhaps a bright spot for the future lies in the evolution of pharmacogenetic approaches for individualized care.   In this book, leading experts from Europe, Australia and the Americas provide a timely appraisal of treatments for the most severely ill schizophrenia patients. This clinically focused  book is informed by the latest research on the neurobiology and treatment of schizophrenia. It is comprehensive in scope, covering current treatment options, various add-on approaches, and a range of psychosocial treatments. The contributors are respected experts who have combined their clinical experience with cutting-edge research to provide readers with authoritative information on fundamental aspects of clinical care for schizophrenia.